Israeli Education Policy How to Move Ahead in Reform - Hemmings, Philip (OECD Economics Department Working Papers, 2010)
Israel's education system is complicated by multiple streams at the primary and secondary levels and by military conscription. Population growth and economic expansion have brought a massive increase in demand for all levels of education. Educational attainment statistics are impressive, but results show high-school students have poor basic skills. Reform efforts to tackle this are underway, including increased teachers' pay in combination with more contact hours and increasing the length of compulsory education. As in other socio-economic spheres, there are significant gaps between Arab-Israelis and the rest of the population. Also, the Ultra-orthodox community's independent education system presents specific concerns and challenges. In tertiary education, progress has been hindered by the collapse of a reform package that envisaged increased state funding combined with increased student tuition fees, expansion of government-backed student loans and a range of other structural reforms. This Working Paper relates to the 2010 OECD Economic Survey of Israel (www.oecd.org/eco/surveys/israel)